Kobiety a ruchy heretyckie według "Diversarum hereseon liber" Filastriusza z Brescii - Szram, Mariusz (Vox Patrum, 2016)
The article discusses two issues related to the role of women in heretical movements on the basis of Philastrius’ of Brescia Diversarum hereseon liber (written between 380 and 388): the place and the importance of the feminine in the doctrinal teaching of the heretics, along women’s participation in setting up and functioning of the various heresies. In the Jewish movements false-beliefs were associated with the figures of pagan goddesses, which some groups worshiped in different periods of the history of Israel. Contrary to the widespread in the ancient culture belief of the relationship of the male element in human person with the intellectual sphere, in the early Christian Gnosticism it was thought that the feminine was the personification of intellect. An example of this phenomenon on the doctrinal plane was the eon “Wisdom” (sapientia), and on the historical one – Helena accompanying Simon Magus, the precursor of all Christian heresy. Among the female characters of biblical inspiration for erroneous views, resulting from improper, sometimes mythologizing exegesis was especially the mother of mankind Eve. However, the creators of heresies didn’t stress clearly her feminine qualities as that might encourage the emergence of their heterodox doctrines. The known names of women – the members of Jewish and early Christian misbelief movements – appear in Philastrius’ index much less often than men. These are individual cases: Helena accompanying Simon Magus, Priscilla and Maximilla – the co-founders of Montanism heresy.